Planificación estratégica y evaluación de la comunicación en Ecuador. Caso de estudio: Corporación Nacional de Telecomunicaciones, CNT empresa pública - Méndez Pesantes, Paulina Alexandra (2014)
Research topic: "Strategic Planning and Evaluation of Communication in Ecuador", is a case study of Public Enterprise National Telecommunications Corporation, and is considered as a model for analyzing the process of Strategic Communication Planning for Measurement and evaluation Campaign: "YOU MORE AND BETTER PRESS" launched in 2013 by the Office of Social Communication, in order to provide professional solutions in line with organizational objectives. Five chapters has been structured for the development of this research, the contents are part of the Institutional, Theoretical, Methodological, Research and Analysis; and Proposals for Improvement. By descriptive exploratory research communication management was diagnosed, it was assessed that the results are aligned with corporate objectives, and improvements to strategic planning is proposed, since the National Telecommunications Corporation, CNT EP, reinforce methods assessment and measurement related to the achievement of the specific objectives of the requesting areas of strategic communication with the general objectives of the organization.